High-Dose Intravenous Immunoglobulin in Severe Coronavirus Disease 2019: A Multicenter Retrospective Study in China - Cao, Wei; Liu, Xiaosheng; Hong, Ke; Ma, Zhiyong; Zhang, Yuelun; Lin, Ling; Han, Yang; Xiong, Yong; Liu, Zhengyin; Ruan, Lianguo; Li, Taisheng (Frontiers in Immunology, 2021)
Background: The effective treatment of COVID-19 remains unclear. We reported successful use of high-dose intravenous immunoglobulin (IVIg) in cases of severe COVID-19, but evidence from larger case series is still lacking. Methods: A multi-center retrospective study was conducted to evaluate the effectiveness of IVIg administered within two weeks of disease onset at a total dose of 2 g/kg body weight, in addition to standard care. The primary endpoint was 28-day mortality. Efficacy of high-dose IVIg was assessed by using the Cox proportional hazards regression model and the Kaplan-Meier curve adjusted by inverse probability of treatment weighting (IPTW) analysis, and IPTW after multiple imputation (MI) analysis. Results: Overall, 26 patients who received high-dose IVIg with standard therapy and 79 patients who received standard therapy only were enrolled in this study. The IVIg group was associated with a lower 28-day mortality rate and less time to normalization of inflammatory markers including IL-6, IL-10 and ferritin compared with the control. The adjusted HR of 28-day mortality in high-dose IVIg group was 0.24 (95%CI 0.06-0.99, p<0.001) in IPTW model, and 0.27 (95%CI 0.10-0.57, p=0.031) in IPTW-MI model. In subgroup analysis, patients with no comorbidities or treated in the first week of disease were associated with more benefit from high-dose IVIg. Conclusions: High-dose IVIg administered in severe COVID-19 patients within 14 days of onset was linked to reduced 28-day mortality, more prominent with those having no comorbidities or treated at earlier stage.